(untitled) (jornal of the libyan geographical society, 2009)
The continent of Africa comprises approximately 50 countries within a unified continental geographical area, in addition to some surrounding island nations such as São Tomé and Príncipe. Africa is distinguished by its unique and distinctive location; it is the only continent situated in such a central position that the equator almost bisects it. Two sections, while the flat northern section extends to form the base of the continental triangle with its Mediterranean coastline, the southern section extends southward to end the continent at the apex of the triangle. The continent of Africa is also characterized by its central location among the continents of the world, and its access to important seas and oceans. Its control over strategic shipping routes and seaports enabled it to play a civilizational and economic role in global geopolitics. While Africa seeks to unify its political efforts and invest its economic resources to form a unified geographical space represented by the African Union in order to be able to enter the era of globalization and compete with the political and economic blocs in the world in the twenty-first century, It faces difficult demographic and environmental problems, numerous economic, social, and health challenges, and multiple ethnic and political conflicts that have exacerbated these problems and hindered its countries from catching up with developed nations. The following pages discuss the most important of these problems and challenges facing the African continent...